Salt Damage and Rising Damp Treatment in Building Structures - J. M. P. Q. Delgado; A. S. Guimarães; V. P. de Freitas; Iñigo Antepara; Václav Kočí; Robert Černý (Advances in Materials Science and Engineering)
Salt damage can affect the service life of numerous building structures, both historical and contemporary, in a significant way. In this review, various damage mechanisms to porous building materials induced by salt action are analyzed. The importance of pretreatment investigations is discussed as well; in combination with the knowledge of salt and moisture transport mechanisms they can give useful indications regarding treatment options. The methods of salt damage treatment are assessed then, including both passive techniques based on environmental control, reduction of water transport, or conversion to less soluble salts and active procedures resulting in the removal of salts from deterioration zones. It is concluded that cellulose can still be considered as the favorite material presently used in desalination poultices but hydrophilic mineral wool can serve as its prospective alternative in future applications. Another important cause of building pathologies is the rising damp and, in this phenomenon, it is particularly severe considering the presence of salts in water. The treatment of rising damp in historic building walls is a very complex procedure and at Laboratory of Building Physics (LFC-FEUP) a wall base hygroregulated ventilation system was developed and patented.